Predicting gifted foreign language learning and performance - Faulkner, Hilary (2003)
This thesis examines individual learner characteristics in order to identify those useful as predictors of gifted foreign language learning performance and creativity in secondary school pupil learners. An individual learner might possess a range of learner characteristics which combine to support his or her gifted foreign language performance. Foreign language learning in England is examined in the opening chapter, providing an historical and educational context within which to explore individual learner differences and the notion of gifted foreign language performance. Theories and research findings from the fields of linguistics are scrutinised together with those generated by foreign language education research in chapter two. Additionally, there is an explanation of giftedness and this latter discussion links to chapter three which relates specifically to gifted performance and creativity in foreign language learning. The Good Language Learner research conducted by Naiman, Frohlich, Stern and Todesco offers a template for studying multiple learner characteristics and the pioneering work of Vygotsky introduces a model for the teaching of the gifted. Chapter four presents the subsequent theoretical framework for this research and clearly differentiates between cognitive and affective individual learner characteristics. Specific research questions focus on selected individual learner characteristics, which include: cognitive ability, foreign language aptitude, motivation and attitude in foreign language learning and these are discussed within chapter five. Quantitative methods are used to address the research questions and data is collected from a group of mixed ability secondary school pupils over a three year period. The research tools included standardised tests for ability, memory, and language aptitude and motivation. Creativity tasks and a questionnaire surveying pupil attitude to foreign language learning were designed for the research in this thesis. The quantitative data was processed statistically. Significant results are highlighted and interpreted with reference to the original theoretical framework and this guides the discussion in chapters six and seven respectively. The closing chapter summarises the main research findings and offers a practical strategy for foreign language teaching including guidelines for the identification of gifted foreign language learners. This is juxtaposed with the current challenging circumstances facing schools, brought about by government educational policy which is seeking to improve pupil performance in foreign language learning and to change national attitudes and perceptions to foreign languages and cultures.